Pelaksanaan Pengaturan Kartu Identitas Anak Sebagai Jaminan Kepastian Hukum Hak Atas Anak Terlantar (Studi Kasus Di Jakarta Selatan) - Budiyono (Law Research Review Quarterly, 2025)
Children are the nation's most valuable assets. They have the constitutional right to grow and develop optimally, and they have the right to be protected from all forms of violence and discrimination. In Indonesia, child protection is guaranteed by the 1945 Constitution and reinforced by the ratification of the Convention on the Rights of the Child. However, the reality is that many children are still neglected and live without an official identity, which prevents them from accessing basic rights such as education, health care, and legal protection. One of the state's efforts to address this issue is the issuance of the Child Identity Card (KIA). This is done through Permendagri Number 2 of 2016. The KIA serves as a legal document that guarantees children's identities and facilitates their access to public services. This study aims to examine the implementation of KIA regulations for neglected children in South Jakarta and identify obstacles to its implementation. The study employs a legal-empirical method with a qualitative approach. The study employs the theories of law enforcement by Robert Seidman and of legal certainty by Gustav Radbruch and Jan Michiel Otto, which assert that law in society is influenced by social, political, economic, and cultural forces. Additionally, the theory of legal certainty emphasizes three core values: justice, legal certainty, and utility. It also highlights the importance of having clear, consistent, and easily accessible legal rules. The research findings indicate that, despite its significant potential to ensure legal protection for abandoned children, the KIA still faces various challenges in implementation, including low public awareness, limited infrastructure, and insufficient coordination among relevant agencies. The study recommends enhancing public education, simplifying administrative procedures, and strengthening cross-sectoral coordination to achieve effective, comprehensive legal protection for abandoned children in Indonesia.